Die personaliteit van vrou-wees binne die Mediterreense kultuur - Dreyer, Yolanda (Hervormde teologiese studies, 1999)
Being a woman in Mediterranean culture. This article is written from the perspective of pastoral care and counseling with women. On account of their training in Biblical studies, pastors are aware of the gap between modem Westem culture and Mediterranean culture in the first century. The question is whether the meaning of this knowledge for the life and faith of women is adequately taken into consideration in pastoral work. In this article an explanation of what is meant by the concept 'culture' is given. The meaning of social identity within Mediterranean culture, being a woman within first-century patriarchy and the different 'categories' of women in this culture are discussed. These aspects are contextualised within the purity system of that culture.